Anterior knee pain after unreamed intramedullary nailing of the tibia - Hossein Fanian; Mohammad Dehghani (Journal of Research in Medical Sciences, 2008)
BACKGROUND: Tibial shaft fracture is the most common type of long bone fractures, and intramedullary nailing is the treatment of choice. Anterior knee pain (AKP) is the most common complication of tibial nailing. The exact etiology of AKP is unknown, and the reported incidence is between 10-86%. Since many activities of daily living of Iranians need kneeling, squatting, and tailor position, knee pain can effectively limit these activities. We decided to evaluate knee pain in patients with tibial shaft fractures treated with unreamed intramedullary nailing in our hospital. METHODS: We evaluated 232 patients between 16-77 year-old with tibial shaft fractures treated with intramedullary nailing from 2005 to 2007 with six months follow up period. RESULTS: According to visual analogue scale (0-10), 165 (71.1%) patients had no pain. Anterior knee pain was mild in 54 (28.9%) cases; 12 (5.2%) cases had moderate pain, and one patient (0.4%) experienced severe pain. The most severe pain was felt in kneeling position and the mildest pain was felt in resting position. CONCLUSIONS: The incidence of moderate to severe AKP in patients who had intramedullary nailing for tibial shaft fractures was relatively low. In view of medicolegal litigation, patients should be aware of this complication. KEYWORDS: Tibia, fracture, knee pain, trauma, internal fixation.